2020
DOI: 10.1089/fpd.2019.2708
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Infection in Mesenteric Lymph Nodes of Breeding Sows

Abstract: Salmonellosis is one of the main foodborne diseases worldwide. Breeding sows asymptomatically infected with Salmonella can transmit the pathogen to piglets and humans. The isolation of Salmonella from mesenteric lymph nodes (MLNs) is considered a demonstration of asymptomatic infection in swine. As previous breeding sow studies have been performed using feces, the aim of this work was to study the occurrence of Salmonella infections by sampling MLNs, in comparison to their serological status. First, Salmonella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…There were four MDR isolates from cervical LN and two from mandibular LN. These results are similar to Salmonella prevalence of 6.1% in mediastinal LN from sows at slaughter in Spain [ 19 ]. In that study, serotypes of isolates were: Typhimurium (43.7%), Derby (18.7%), Enteritidis (12.5%), and Montevideo (12.5%) with 9/16 of isolates showing multi-resistance to three or more antimicrobial classes (SSuT, ACSSut, and ASSut-Nx-Cfx).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…There were four MDR isolates from cervical LN and two from mandibular LN. These results are similar to Salmonella prevalence of 6.1% in mediastinal LN from sows at slaughter in Spain [ 19 ]. In that study, serotypes of isolates were: Typhimurium (43.7%), Derby (18.7%), Enteritidis (12.5%), and Montevideo (12.5%) with 9/16 of isolates showing multi-resistance to three or more antimicrobial classes (SSuT, ACSSut, and ASSut-Nx-Cfx).…”
Section: Resultssupporting
confidence: 84%
“…The decreased Salmonella isolation rates (0.73%) of Plant B in the present study mirror those of 0% reported for superficial cervical LN [ 17 ] and 0.06% for subiliac LN [ 18 ] of market hogs in U.S. plants. Although not peripheral LN, similar Salmonella prevalence results (6.1%) were reported for mesenteric LN from breeder sows in Spain [ 19 ].…”
Section: Resultssupporting
confidence: 79%
“…For this reason, detecting risk factors associated with the presence of Salmonella in the primary sector is essential for designing mitigation strategies. Additionally, it is interesting that only the monophasic variant was recovered herein, while Salmonella Typhimurium (4,5:12:i:1,2) was the most prevalent serovar detected in fattening pigs and sows within intensive systems [ 11 , 12 , 29 ]. Furthermore, the most common serovars reported in Iberian pigs were Anatum and Typhimurium with resistance to streptomycin and tetracycline [ 25 ], differing from those described in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella isolation procedures were performed according to ISO 6579:2002/Amd 1:2007 (ISO) rules [ 10 ], as previously described [ 11 , 12 , 13 ]. All culture media and reagents used were purchased from Laboratorios Conda S.A., Spain.…”
Section: Methodsmentioning
confidence: 99%
“…Salmonellosis is one of the most frequent foodborne zoonotic diseases, characterised by abdominal cramps, diarrhoea, fever and vomiting, constituting a worldwide major public health concern [1]. Breeding sows asymptomatically infected with Salmonella can be naturally transmitted directly or indirectly between animals and humans, for example through the consumption of contaminated animal derived food or through contact with infected animals [2].…”
Section: Introductionmentioning
confidence: 99%